The history of Middle-Earth III - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Houghton Mifflin Harcourt, 2020)
This volume comprises the final three parts of The History of Middle-earth and represents manuscripts related to the later history of The Silmarillion, written after Tolkien had completed The Lord of the Rings, together with an account of the writing of he Prologue and Appendices to The Lord of the Rings, in which the historical structure of the Ages that links these two works actually emerged.